Academic Performance of Children With Sickle Cell Disease in the United States: A Meta-Analysis - Heitzer, Andrew M.; Hamilton, Latacha; Stafford, Claire; Gossett, Jeffrey; Ouellette, Lara; Trpchevska, Ana; King, Allison A.; Kang, Guolian; Hankins, Jane S. (Frontiers in Neurology, 2021)
Background: Students with sickle cell disease are at risk for poor academic performance due to the combined and/or interactive effects of environmental, psychosocial, and disease-specific factors. Poor academic performance has significant social and health consequences. Objective: To study academic achievement and attainment in children with sickle cell disease. Design: Medline, Embase, SCOPUS, CINAHL, ERIC, and PsycINFO were searched for peer-reviewed articles. Studies of children (ages 5-18) diagnosed with sickle cell disease of any genotype reporting academic achievement (standardized tests of reading, math, and spelling) or attainment (grade retention or special education) outcomes were included. Outcomes were analyzed using a random effects model. Achievement scores were compared to within study controls or normative expectations. Prevalence of grade retention and special education services were compared to national estimates for Black students. Age at assessment and overall IQ were evaluated separately for association with reading and mathematics scores. Subgroup analyses of reading and math scores were analyzed by cerebral infarct status (no cerebrovascular accident, silent infarct, stroke). Results: There were 44 eligible studies. Students with sickle cell disease scored 0.70, 0.87, and 0.80 (p<0.001) SD below normative expectations on measures of reading, mathematics, and spelling, respectively. Compared to unaffected sibling and/or healthy controls (k =8, n=508), reading and math scores were 0.40 (p=0.017) and 0.36 (p=0.033) SD below expectations. Grade retention was approximately 10 times higher in students with sickle cell disease than Black students nationally. Intellectual functioning explained 97.3% and 85.8% of the variance in reading and mathematics performance, respectively (p<0.001). Subgroup analyses revealed significant differences in reading (p=0.034) and mathematics (p<0.001) based on infarct status, with lower performance associated with presence of a silent infarct or stroke. Conclusion: Students with sickle cell disease demonstrate notable academic difficulties and are at high risk for grade retainment. Development of academic interventions and increased access to school support services are needed for this vulnerable population.